1999
DOI: 10.2175/106143098x121716
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of One‐Step Acidic Extraction Versus Two‐Step Basic and Acidic Extraction Procedures for Semivolatile Analysis of Wastewater

Abstract: The feasibility of using the U.S. Environmental Protection Agency's (U.S. EPA's) contract laboratory protocol method for analyzing semivolatile compounds in industrial wastewater pretreatment program samples was investigated because of time and labor savings involved. Various laboratory evaluation studies were conducted to determine whether this alternate one‐step acidic extraction method would give comparable results to U.S. EPA Method 625. These studies consisted of comparisons of method detection limits, sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…May and Halpern [11] did provide an alternative one step mechanism in which "cyclic" activated complex was formed which disproportionates to give products that are consistent with (6). The authors [11] were of the opinion that both the chain multistep mechanism proposed in (1)-(4) and the onestep mechanism, as shown in (8) in Scheme 1, were plausible mechanisms. It is the desire of this study to investigate whether the popular multistep mechanism [11,12] or the latter proposed one-step mechanism is the most plausible one and/or if both routes are possible, which would be the most favored:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…May and Halpern [11] did provide an alternative one step mechanism in which "cyclic" activated complex was formed which disproportionates to give products that are consistent with (6). The authors [11] were of the opinion that both the chain multistep mechanism proposed in (1)-(4) and the onestep mechanism, as shown in (8) in Scheme 1, were plausible mechanisms. It is the desire of this study to investigate whether the popular multistep mechanism [11,12] or the latter proposed one-step mechanism is the most plausible one and/or if both routes are possible, which would be the most favored:…”
Section: Resultsmentioning
confidence: 99%
“…The effort of study to shift the chemistry in a different direction was only partially successful. Several others [5][6][7][8][9] have also reported that the reactions of 1,2-diphenylhydrazine and its derivatives were pH dependent and would yield different products depending on the PH of the reaction medium. These studies [4][5][6][7][8][9] concluded that 1,2-diphenylhydrazine and its derivatives enjoy complicated chemistries that include structural rearrangement and disproportionation and that their interactions with metal ions or inorganic substances are complex and incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A kinetic model of the process was discussed. Khalil et al (1999) compared the two-step basic and acidic extraction procedure of US EPA method 625 with the one-step acidic extraction of the US EPA's contract laboratory protocol for analysis of semivolatile constituents in wastewater.…”
Section: New Sample Preparation Techniques and Data Analysismentioning
confidence: 99%